2016
DOI: 10.1080/0284186x.2016.1198493
|View full text |Cite
|
Sign up to set email alerts
|

High tumor mast cell density is associated with longer survival of colon cancer patients

Abstract: Background: Inflammatory cells and inflammatory mediators play an important role in colorectal cancer (CRC). Previous studies have shown that CRC patients with increased expression of cysteinyl leukotriene receptor 1 (CysLTR1) have a poorer prognosis, and Cysltr1 À/À mice display fewer intestinal polyps. However, the role of mast cells (MCs) in colon cancer progression remains unclear. The aim of the present study was to explore the relevance of MCs in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
(46 reference statements)
0
40
0
1
Order By: Relevance
“…Heterogeneous prognostic roles of MCs were found in different cancers . In CRC, several studies have investigated the relationship between MCs and prognosis with conflicting conclusions . Acikalin et al ., Gulubova and Vlaykova and Malfettone et al .…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous prognostic roles of MCs were found in different cancers . In CRC, several studies have investigated the relationship between MCs and prognosis with conflicting conclusions . Acikalin et al ., Gulubova and Vlaykova and Malfettone et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that 5-LO derived products other than LTB 4 could have a direct promotional activity on intestinal tumors. Consistent with these observations, cystinyl leukotriene receptor 1 (CysLT1) deficient mice in the Apc Min/+ background were also shown to display reduced tumor burden [87]. …”
Section: Leukotriene B4 In Cancermentioning
confidence: 87%
“…Furthermore, IL-5, which can be produced by mast cells and eosinophils, has been shown to promote eosinophil infiltration into tumors and suppress tumor metastasis [51]. We have previously shown that an increased mast cell density has been associated with a better prognosis in colorectal cancer patients, and an increased mast cell number was seen in tumors of AOM/DSS Cysltr1 −/− mice [52]. Taken together, the increased mast cell number and increased IL-5 serum levels indicate a more favorable outcome for Cysltr1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%